The Effect Of The Learning Environment And Emotional Intelligence On Academic Performance Of Management Students, Faculty Of Economics And Business Tadulako University - Annisa Savira; Idris Idris; Andi Indriani Ibrahim; Pricylia Chintya Dewi Buntuang (UNIVED Press, 2026)
This study aims to examine the effect of the learning environment and emotional intelligence on the academic performance of undergraduate Management students at the Faculty of Economics and Business, Tadulako University. A quantitative approach was employed using a survey method. The sample consisted of 82 students selected through purposive sampling based on the 2021–2023 cohorts. Data were collected using a Likert-scale questionnaire and analyzed with multiple linear regression using SPSS version 27. The results indicate that the learning environment has a positive and significant effect on students’ academic performance. Emotional intelligence was also found to have a positive and significant effect on academic performance. Furthermore, both variables jointly contribute meaningfully to improving students’ academic outcomes. These findings suggest that a supportive campus learning environment, together with students’ ability to regulate their emotions and engage in positive interactions, plays an important role in helping them achieve optimal academic performance.